2019
DOI: 10.21608/ejfsat.2016.41640
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Teratogenic Effects of Antiepileptic Drugs: Lamotrigine and Levetiracetam on Adult Albino Rats

Abstract: Background: Lamotrigine (LTG) and levetiracetam (LEV) are widely and increasingly prescribed second generation antiepileptic drugs for women with epilepsy during childbearing age. However, data pertaining to their congenital malformations are lacking. Aim: This study aimed to investigate and compare the teratogenic effects of LTG and LEV on normal adult female albino rats and their fetuses in order to find out the least teratogenic one of them. Materials and methods: Ninety-six adult albino rats (64 virgin fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Padmanabhan et al (2003) reported that administering lamotrigine as single dose of 50-200 mg/kg body weight can induce intrauterine growth retardation in mice, whereas multiple doses of 25, 50, 75 mg/kg body weight caused a dose dependent increase in embryonic resorption and craniofacial malformations. Mohanty et al (2011) and Elgndy et al (2016) showed an increase in the ventricular size in lamotrigine exposed rat fetus.…”
Section: Discussionmentioning
confidence: 95%
“…Padmanabhan et al (2003) reported that administering lamotrigine as single dose of 50-200 mg/kg body weight can induce intrauterine growth retardation in mice, whereas multiple doses of 25, 50, 75 mg/kg body weight caused a dose dependent increase in embryonic resorption and craniofacial malformations. Mohanty et al (2011) and Elgndy et al (2016) showed an increase in the ventricular size in lamotrigine exposed rat fetus.…”
Section: Discussionmentioning
confidence: 95%